Methodologies of teaching and training in higher educational institutions of the EU and Ukraine - ZHURAVSKA, Nina (Journal of Education, Technology and Computer Science, 2014)
Why you need a teacher in high school, just as the carrier and transmitter of information? But it is in this capacity he is much inferior to many other sources of information such as books and computers. Higher education institution serves not only and may be not so much for the transfer specialized knowledge but for the development and reproduction of specific cultural group, the most important element of which is itself a specialist. He is characterized as a representative of a particular culture not only a specific set of knowledge and skills, but also a certain worldview, life attitudes and values, especially the of professional conduct and others. So the teacher not only sends the student knowledge and professional skills, and attaches it to a specific culture, and that this culture was developed and reproduced needed live people, live human communication. This truth more than a hundred years ago formulated by K. D. Ushinsky: “Only a person can act on the development and definition of personality, only nature can be used to form the character” [Ушинский 1984: 78–83].